Experimental Assessment Of The Effect Of Rutan On The Level Of Endogenous Intoxication Syndrome In Prepubertal An - Ziyaviddin Zainutdinovich Hakimov; Fatima Adilbaevna Khalmuratova; Alisher Khudayberdievich Rakhmanov (Zien Journals, 2025)
An acute hepatitis model was induced in one-month-old rabbits using carbon tetrachloride, followed by experimental therapy with Karsil and Rutan to evaluate their effectiveness in eliminating endogenous intoxication syndrome. It was found that acute toxic hepatitis in prepubertal rabbits is accompanied by a high degree of endotoxemia, which manifests as an increase in the sorption capacity of erythrocytes, the concentration of middle molecular weight molecules in the blood, and a reduction in the lifespan of paramecia. Experimental treatment of acute hepatitis with Karsil, and especially with Rutan, led to normalization of the parameters of endogenous intoxication syndrome to levels comparable to those of healthy animals. Rutan may be recommended as a therapeutic agent for the treatment of conditions accompanied by endotoxemia in pediatric practice, following appropriate clinical trials
Keywords: prepubertal period; acute toxic hepatitis; endogenous intoxication syndrome